Pengatur Tegangan AC Tiga Fasa dengan Kontrol Rangkaian Analog - effendi, effendi; zakwansyah (J-Innovation, 2025)
One of the topics studied in the Power Electronics course is the three-phase AC to AC converter, where the output frequency remains the same as the source voltage frequency, but the output voltage magnitude can be adjusted according to the requirements, this circuit is often referred to as a three-phase AC voltage regulator. The SCR trigger circuit functions to control the three-phase AC voltage, using six SCRs in total. The components used include an LM324, which functions as a comparator, MOC3063, diodes, and several other analog electronic components. The three-phase AC voltage source in this study uses a low-voltage supply, which is also used as a reference point for the comparator circuit, therefore, a three-phase step-down transformer circuit is required. The measurement of the output waveforms Van, Vbn, and Vcn is conducted using a digital oscilloscope with SCR triggering delay times of 1.6 ms (28.8°), 2.5 ms (45°), 3.5 ms (59.4°), 5 ms (90°), 6.6 ms (118.8°), and 7.5 ms (135°). The measured waveform characteristics align with the results obtained using computer simulations. However, the differences between the measurement results and mathematical calculations are relatively small. This is due to the manual method used to determine the triggering time by adjusting the potentiometer, which introduces the possibility of errors during measurements performed by different individuals.